2023
DOI: 10.1186/s12885-023-11078-9
|View full text |Cite|
|
Sign up to set email alerts
|

Patient-derived organoids for precision oncology: a platform to facilitate clinical decision making

Abstract: Background Despite recent advances in research, there are still critical lacunae in our basic understanding of the cause, pathogenesis, and natural history of many cancers, especially heterogeneity in patient response to drugs and mediators in the transition from malignant to invasive phenotypes. The explication of the pathogenesis of cancer has been constrained by limited access to patient samples, tumor heterogeneity and lack of reliable biological models. Amelioration in cancer treatment dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…A single PDO model may not fully capture the complexity of an entire tumor because intra-tumor heterogeneity can lead to varying growth patterns and drug responses, making clinical applications more complicated ( Ramon et al, 2020 ; Bose et al, 2021 ). Another crucial aspect is long-term viability and functionality, which require a deep understanding of the tumor microenvironment, including stromal interactions and nutrient signaling ( Gjorevski et al, 2016 ; Chitrangi et al, 2023 ).…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…A single PDO model may not fully capture the complexity of an entire tumor because intra-tumor heterogeneity can lead to varying growth patterns and drug responses, making clinical applications more complicated ( Ramon et al, 2020 ; Bose et al, 2021 ). Another crucial aspect is long-term viability and functionality, which require a deep understanding of the tumor microenvironment, including stromal interactions and nutrient signaling ( Gjorevski et al, 2016 ; Chitrangi et al, 2023 ).…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…Herein, we summarized recent clinical studies that utilized PCa organoids and model systems for evaluating the novel therapies for PCa diseases (Table 2). These studies included the clinical trials conducted at Centre Antoine Lacassagne in France (NCT03952793) [121], The Christie NHS Foundation Trust in the UK (NCT04723316) [122], the Netherlands Cancer Institute in the Netherlands (NCT02695459), Fudan University in China (NCT04927611) [123], SpeciCare, Georgia, USA (NCT03896958) [124], and the Rutgers Cancer Institute in New Jersey (NCT02458716) [36] (Table 2). Recently, a PDO-based model was employed in a Phase II trial (NCT01799278) for investigating the efficacy of the aurora kinase inhibitor Alisertib (MLN8237) for mCRPC and NEPC.…”
Section: Clinical Implications and Therapeutic Approachmentioning
confidence: 99%
“…For instance, PDX research has led to the discovery of alternative immune checkpoints and changes in antigen presentation, shaping the development of combination therapies and influencing clinical treatment modifications. Such studies have also identified biomarkers predictive of treatment response, allowing for the adaptation of clinical protocols [155].…”
Section: Clinical Implications and Translational Approachesmentioning
confidence: 99%
“…Insights gained from PDX studies have informed the enrollment of patients in trials for new targeted agents, leading to improved outcomes. These translational models are thus integral to the evolution of personalized medicine, enhancing the specificity and adaptability of cancer therapies [155].…”
Section: Clinical Implications and Translational Approachesmentioning
confidence: 99%